The distribution of factorization patterns on linear families of polynomials over a finite field - Cesaratto, Eda (2017)
We estimate the number |Aλ| of elements on a linear family A of monic polynomials of Fq[T] of degree n having factorization pattern λ:=1λ12λ2nλn. We show that |Aλ| = T(λ)qn-m + O(qn-m-1/2), where T(λ) is the proportion of elements of the symmetric group of n elements with cycle pattern λ and m is the codimension of A. Furthermore, if the family A under consideration is “sparse”, then |Aλ|=T(λ)qn-m+O(qn-m-1). Our estimates hold for fields Fq of characteristic greater than 2. We provide explicit upper bounds for the constants underlying the O-notation in terms of λ and A with “good” behavior. Our approach reduces the question to estimate the number of Fq-rational points of certain families of complete intersections defined over Fq. Such complete intersections are defined by polynomials which are invariant under the action of the symmetric group of permutations of the coordinates. This allows us to obtain critical information concerning their singular locus, from which precise estimates on their number of Fq-rational points are established.